2021
DOI: 10.1021/acsearthspacechem.1c00071
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Enhances Leaching of Ferrous Ions but Hinders Reductive Dissolution of Ferric Ions from Iron Oxides

Abstract: Iron governs biological activities in the natural environment as an essential element. Although the concentrations of dissolved iron species are primarily regulated by the solubility of iron minerals, there are additional pathways of the supply of dissolved iron species from solids. Redox processes play important roles in the dissolution of iron species from minerals because ferrous ions are more soluble than ferric ions. In addition, recent studies have indicated that freezing enhances the dissolution of iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This is especially important given the recent (Lepre and Olsen, 2021); thus, surface reddening could have a strong paleoclimate significance. Alternatively, freezethawing in proglacial systems could influence redox dynamics and lead to the preferential release of ferrous iron (Doi et al, 2021). Importantly, hematite persists and was detected by XRD in most green samples from across the study area (Figure 7), indicating they would have initially been red or otherwise experienced oxidation prior to green/bleaching alteration.…”
Section: Iron and Titanium Oxides Suggest Post-depositional Oxidationmentioning
confidence: 99%
“…This is especially important given the recent (Lepre and Olsen, 2021); thus, surface reddening could have a strong paleoclimate significance. Alternatively, freezethawing in proglacial systems could influence redox dynamics and lead to the preferential release of ferrous iron (Doi et al, 2021). Importantly, hematite persists and was detected by XRD in most green samples from across the study area (Figure 7), indicating they would have initially been red or otherwise experienced oxidation prior to green/bleaching alteration.…”
Section: Iron and Titanium Oxides Suggest Post-depositional Oxidationmentioning
confidence: 99%
“…We recently showed that freezing enhances the leaching of ferrous ions but hinders the reduction of ferric ions in iron oxides. 17 It was also reported that, in the natural process, iron or manganese contained in the particles is reduced to a soluble form by the entrainment of particles in the grain boundary space. 18 Thus, the dissolution of metal ions from the particulate matter by freezing is an important process that may provide bioavailable trace metal elements.…”
Section: ■ Introductionmentioning
confidence: 99%
“…According to their study, coexistent chloride affects the redox reaction of Ag + during the freeze–thaw process. We recently showed that freezing enhances the leaching of ferrous ions but hinders the reduction of ferric ions in iron oxides . It was also reported that, in the natural process, iron or manganese contained in the particles is reduced to a soluble form by the entrainment of particles in the grain boundary space .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical approaches including voltammetry are also attractive strategies for monitoring the chemical reactions in FCSs. Okada and coworkers reported the dissolution of ferrous ions from iron oxide (20) and viologens, (21) elucidated by cyclic voltammetry. Although electrochemical approaches can elucidate kinetic and thermodynamic parameters, it is still challenging to control the area of the surface in contact with an FCS and to obtain distribution maps of the chemical species therein when working electrodes are used.…”
Section: Introductionmentioning
confidence: 99%